The object tracking algorithm using dimensional based detection for public street environment - Matveev, I.G.; Karpov, K.A.; Yurchenko, A.V.; Siemens, E. (of the E.A. Buketov KarU publ., 2020)
The paper proposes an approach to object tracking for public street environments using dimensional based object detection algorithm. Besides the tracking functionality, the proposed algorithm improves the detection accuracy of the dimensional based object detection algorithm. The proposed tracking approach uses detection information obtained from multiple cameras which are structured as a mesh network. Conducted experiments performed in a real-world environment have shown 10 to 40 percent higher detection accuracy that has proved the proposed concept. The tracking algorithm requires negligible computational resources that make the algorithm especially applicable for low-performance Internet of things infrastructure.
Keywords: object tracking; smart city; object detection; street lighting